Solution,
Let P = ( x, -x + 6) = (x, 6 - x)
We want to solve this
( Distance from P to (0,0) )^2 = (Distance from P to (10, -10) )^2
x^2 + (6 - x)^2 = [ ( x - 10)^2 + ( 6 - x + 10)^2
x^2 + x^2 - 12x + 36 = x^2 - 20x + 100 + x^2 - 32x + 256 simplify
-12x + 36 = -52x + 356
40x = 320
x = 8
And y = -(8) + 6 = -2
So...P = ( 8, -2)
In mathematics, an equation is an equation that expresses two equations by joining them with an equal sign =. Equations in other languages and the word their relatives can have slightly different meanings; for example, in French, an equation is defined as containing one or more variables, but in English, it is an equal sign.
A well-formed expression consisting of two combined equations is an equation, and a variable makes the equation true. The variable for which the equation must be solved is also called the unknown, and the value of the unknown that satisfies the equation is called the solution of the equation. There are two types of equations: identities and constraint equations. The ID applies to all values of the variable. Constraint equations apply only to specific values of variables
Learn more about Equations here: brainly.com/question/2972832
#SPJ4
Step-by-step answer:
The domain of log functions (any legitimate base) requires that the argument evaluates to a positive real number.
For example, the domain of log(4x) will remain positive when x>0.
The domain of log_4(x+3) requires that x+3 >0, i.e. x>-3.
Finally, the domain of log_2(x-3) is such that x-3>0, or x>3.
Answer:
f(0)=-2
Step-by-step explanation:
We are given that f(x)=3x-2
And we are asked to determine f(0)
In order to do so, we will replace x with 0 in our function
Hence
f(0) = 3(0)-2
f(0)=0-2
f(0)=-2
6,7,9 is not ringt triangle
18,32,40 is not right triangle
24,32,40 is right triangle
10,24,26 is right triangle
Since that f is continuous for all x in R, and f > 0 then
![\lim\limits_{x\to -\infty}3^x+4=4](https://tex.z-dn.net/?f=%5Clim%5Climits_%7Bx%5Cto%20-%5Cinfty%7D3%5Ex%2B4%3D4)
for hence the asymptote is
y = 4